How Can Biodigesters Help Drive the Circular Economy? An Analysis Based on the SWOT Matrix and Case Studies - Cortez, Suzy C. [UNESP]; Cherri, Adriana C. [UNESP]; Jugend, Daniel [UNESP]; Jesus, Gessica M. K. [UNESP]; Bezerra, Barbara S. [UNESP] (MDPI, 2022)
The use of biodigesters and the circular economy (CE) has been gaining attention in recent years. Both biodigesters and CE have the potential to minimize negative impacts—not only environmental, but also economic and social. However, little attention has been paid to the relationship between biodigesters and CE. Therefore, the objective of this paper is to identify and analyze the implications of the use of biodigesters in the light of a CE concept. To do this, a SWOT matrix was developed based on the opinion of experts and two case studies were conducted in companies operating in different sectors in Brazil. The results showed that the use of biodigesters can drive CE through biogas, which is a renewable energy source, closing the cycle of organic materials, increasing the economic power of companies and small producers, improving basic sanitation in remote areas, and stimulating industrial symbiosis. However, this study identified barriers in the use of biodigesters in the context of CE, such as lack of government incentives and composting being shown to be more cost-effective than the use of biodigesters for the treatment of solid waste.
Keywords: biodigesters; circular economy; industrial ecology; sustainability; sustainable development; waste management